The influence of cross-linking density on the efficiency of post-synthetic sulfonation of hyper-cross-linked polymers and their adsorption capacity for antibiotic pollutants - Wolska, Joanna; Muńko, Malwina; EL, Siblani Hussein; Telegeiev, Igor; Frankowski, Marcin; Szwajca, Anna; Walkowiak-Kulikowska, Justyna; El-Roz, Mohamad; Wolski, Łukasz (Elsevier, 2023)
Hyper-cross-linked polymers (HCPs) attract increasing attention as promising adsorbents for removal of organic pollutants from water. The present work reveals for the first time that the efficiency of the post-synthetic sulfonation of HCPs-based adsorbents and their reactivity in removal of selected polar antibiotic pollutants can be simply controlled by adjusting the cross-linking density of the polymer network. The study included both the evaluation of the mechanism and kinetics of the adsorption process over sulfonated HCPs, as well as the determination of their stability, recyclability, and affinity toward various antibiotics. The latter was established based on adsorption tests using mono- and multicomponent mixtures of different structure antibiotics (ciprofloxacin, tetracycline, sulfamethoxazole and amoxicillin). The adsorption capacity of all sulfonated polymers was found to be directly proportional to the concentration of −SO3H functions and inversely proportional to the cross-linking density of the parent HCPs. The most promising sulfonated polymer had approximately 4 times higher adsorption capacity toward ciprofloxacin than commercial carbon-based adsorbent Norit (427.5 vs. 110.5 mg/g, respectively). The main adsorption mechanism over sulfonated HCPs was chemisorption of the antibiotics via ionic interactions with surface -SO3H groups. Spent adsorbent could be successfully recycled ten times without any loss in its efficiency.
Keywords: hyper-cross-linked polymers; sulfonic acid functionalization; water purification; antibiotic